2008
DOI: 10.1158/1078-0432.ccr-07-4338
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 10 and Cytokeratin 19: Predictive Markers for Poor Prognosis in Hepatocellular Carcinoma Patients after Curative Resection

Abstract: Purpose: Cytokeratin 10 (CK10) was found to be expressed differently in human hepatocellular carcinoma (HCC) cell lines with different metastatic potentials in our previous research.The aim of this study was to assess the value of CK10 alone or in combination with cytokeratin 19 (CK19) in predicting tumor recurrence after curative resection in HCC patients. Experimental Design: CK10 expression in stepwise metastatic HCC cell lines and tumor tissues from 50 HCC patients was investigated using immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 50 publications
4
108
1
1
Order By: Relevance
“…8,11,12 In accordance with these reports, CK19 positivity significantly correlated with the 2-year DFS rate. 8,11 Although the 5-year DFS and OS rate was not significantly correlated with CK19 positivity in this study, both of them tended to be lower in CK19-positive HCC group. Because this study dealt with relatively limited number of cases and the follow up periods were not sufficient, a significant difference might not be obtained.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…8,11,12 In accordance with these reports, CK19 positivity significantly correlated with the 2-year DFS rate. 8,11 Although the 5-year DFS and OS rate was not significantly correlated with CK19 positivity in this study, both of them tended to be lower in CK19-positive HCC group. Because this study dealt with relatively limited number of cases and the follow up periods were not sufficient, a significant difference might not be obtained.…”
Section: Discussionsupporting
confidence: 86%
“…In most of the EGF and CK19-positive HCC N Yoneda et al CK19-positive cases, CK19 expression in HCC was not diffusely observed, and CK19-positive cells were aggregated in focal areas in a single section (Figure 6b). On the basis of previous reports, 8,11,12 CK19-positive HCC was defined as such tumor that o5% of total carcinoma cells showed positive immunoreactivity of CK19 in this study. According to this definition, 9 (12%) of 78 cases of surgically resected HCC samples corresponded to CK19-positive HCC.…”
Section: Expression Of Ck19 Egf Egfr and Jnk In Human Hcc Tissuesmentioning
confidence: 93%
See 1 more Smart Citation
“…Lee et al showed significant survival differences between HCC patients with a hepatocyte-like phenotype and a hepatoblast-like phenotype [70,71] . Other studies suggest that HCC positive for Keratin 19 (KRT19), which is a progenitor cell marker, have a higher rate of recurrence after resection or transplantation [72][73][74] . Other fetal markers such as AFP and epithelial cell adhesion molecule (EpCAM) are of prognostic value as well, since EpCAM+/AFP+HCC is associated with poor survival [75] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 99%
“…[2][3][4][5][6] In 2006, our group was the first to describe the clinicopathological and prognostic relevance of K19 in a Caucasian series of HCCs as it was linked with a high recurrence after transplantation. 7 Subsequently, we started a prospective study on a Caucasian series of 242 consecutive HCC samples with a different range of aetiologies and performed a detailed evaluation of the clinicopathological relevance of K19.…”
Section: What Are the New Findings?mentioning
confidence: 99%